Comparative analysis of the outcome between aperture and suspensory graft fixation methods in anterior cruciate ligament reconstruction surgeries: a systematic review - Bhatt, Priyank R.; Devpura, Mukesh M.; Rathi, Pranav P.; Sable, Aashiket S. (International Journal of Research in Orthopaedics, 2024)
Human knee joint is a complex hinge joint which is relatively unstable compared to other joints of the body. The ligaments of the knee stabilize the joint during the different range of motion and are under continuous tension. This results in anterior cruciate ligament (ACL) being injured during unnatural movement of the joint particularly in sports. With the advent of arthroscopy and better understating of ligament injuries with the use of MRI, the ligament reconstruction procedures have increased. The Reconstructive procedures for the ACL impart use of an Autograft which is secured in the bony tunnels of femur and tibia using various methods. As with any fixation these materials are subjected to various biological and mechanical forces. Suspensory or aperture graft fixation are the two most commonly employed methods in recent times. Both these methods have different tensile strengths and failure rates. Various studies have been conducted to assess the outcomes of these methods to evolve the most suitable and fail-safe method of securing the ACL allograft in the bony tunnels.